PECULIARITIES OF DAILY ECG CHANGES IN PATIENTS WITH ESSENTIAL HYPERTENSION OF THE SECOND STAGE - Ivankova, A.V.; Kuzminova, N.V.; Lozinsky, S.E.; Havryliuk, A.O.; Knyazkova, I.I.; Ivanova, E.I. (World of Medicine and Biology, 2020)
The total of 156 patients (65 men and 91 women) with stage II hypertension were examined. The main clinical group included 124 persons with the evidence of frequent supraventricular or ventricular extrasystole according to the daily Holter ECG monitoring data. Patients with stage II hypertension but without cardiac arrhythmias (32 persons) were the comparison group. It was established that the persistent pattern of the supraventricular extrasystole, which occurred in 36.5 % of patients with essential hypertension, was more common than the persistent pattern of ventricular extrasystole (6 %, p